2011
DOI: 10.1097/aud.0b013e318202e982
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear Dead Regions in Typical Hearing Aid Candidates: Prevalence and Implications for Use of High-Frequency Speech Cues

Abstract: We investigated the prevalence of cochlear dead regions in listeners with hearing losses similar to those of many hearing aid wearers, and explored the impact of these dead regions on speech perception. Prevalence of dead regions was assessed using the Threshold Equalizing Noise test (TEN(HL)). Speech recognition was measured using high-frequency emphasis (HFE) Quick Speech In Noise (QSIN) test stimuli and low-pass filtered HFE QSIN stimuli. About one third of subjects tested positive for a dead region at one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
38
1
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 33 publications
5
38
1
1
Order By: Relevance
“…While the same relationship was observed when NFC was compared to RBW, this relationship was only statistically significant with the removal of one outlier. Our results support the notion that listeners with greater hearing loss in the high frequencies are less able to take advantage of greater bandwidth, potentially due to factors such as dead regions (Mackersie et al, 2004 but see Cox, 2011; Preminger et al, 2005) or less contribution of audibility to speech recognition for listeners with greater hearing loss (Ching et al, 1998, 2001; Hogan & Turner, 1998; Hornsby et al, 2011). However, our data differ from Souza et al (2013) who found that those with greater hearing loss were more likely to show improved speech recognition with NFC.…”
Section: Discussionsupporting
confidence: 84%
“…While the same relationship was observed when NFC was compared to RBW, this relationship was only statistically significant with the removal of one outlier. Our results support the notion that listeners with greater hearing loss in the high frequencies are less able to take advantage of greater bandwidth, potentially due to factors such as dead regions (Mackersie et al, 2004 but see Cox, 2011; Preminger et al, 2005) or less contribution of audibility to speech recognition for listeners with greater hearing loss (Ching et al, 1998, 2001; Hogan & Turner, 1998; Hornsby et al, 2011). However, our data differ from Souza et al (2013) who found that those with greater hearing loss were more likely to show improved speech recognition with NFC.…”
Section: Discussionsupporting
confidence: 84%
“…The gain in music quality with band-limited amplification was much greater, from 4.4 to 8.2. These findings are consistent with results from previous studies (e.g., Yanz 2002; Hornsby & Ricketts, 2006; Hornsby & Ricketts, 2006; Gordo & Lorio 2007; Moore 2009; Cox et al 2011; Hornsby et al, 2011) showing that if sufficient gain is applied to the high-frequency components of speech, those components may mask the lower-frequency components due to downward spread of masking (e.g., Yanz 2002; Hornsby & Ricketts, 2006; Gordo & Lorio 2007; Moore 2009; Cox et al 2011). In this case of bimodal stimulation, this may limit the bimodal benefit.…”
Section: Discussionsupporting
confidence: 92%
“…These listeners typically have a dead region, or regions, in the parts of the non-implanted cochlea responding to medium and high frequencies. Amplification of frequencies inside the dead region(s) sufficient to restore audibility, may cause downward spread of masking, unwanted distortion, and increased acoustic feedback (e.g., Yanz 2002; Hornsby & Ricketts, 2006; Gordo & Lorio 2007; Moore 2009; Cox et al 2011), which may compromise the benefit of combining the amplified, acoustic signal and the electric signal. At issue in this project was the frequency range over which acoustic amplification should be provided to yield the best speech understanding and speech/sound quality for listeners receiving bimodal stimulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the TEN test the number of subjects with DRs among our screened subjects with HFloss (n=105) was 15 (unilateral DRs) and 33 (bilateral DRs); which is in total 46 % Differences in study design and subjects make a direct comparison with earlier studies difficult, but the prevalence of DRs seems similar to that reported by Preminger et al (2005) and Cox et al (2011).…”
Section: Discussionmentioning
confidence: 83%